MUSLIMAH AESTHETIC EDUCATION AS AN INTEGRATED LEARNING STRATEGY FOR SECONDARY LEVEL FEMALE STUDENTS IN THE ERA OF THE DEATH OF EXPERTISE - Feryani, Elsa; Handrianto, Budi; Syafrin, Nirwan (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The era of the